2008
DOI: 10.3390/ijerph5030152
|View full text |Cite|
|
Sign up to set email alerts
|

Sanitary Conditions of Public Swimming Pools in Amman, Jordan

Abstract: This study was carried out in the summer of 2005 and investigated all of active public swimming pools (85 out of 93) in Amman, the capital of Jordan. The aim of this study was to find out if these swimming pools are in compliance with Jordanian Standards for Swimming Pools Water (JS 1562/2004). The pools were surveyed against the water microbial quality and other physicochemical parameters indicated in the standards. Two samples from each pool were collected for microbial analysis and pools monitoring were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Other factors also have been implicated including time of sampling, water temperature, and load of swimmers (Rabi, Khader, Alkafajei, & Aqoulah, 2008). Two previous authors have failed to find any association between bacterial contamination and the pH of the water in swimming pools (Esterman et al, 1984;Rabi et al, 2008). The current research confirmed this lack of association.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Other factors also have been implicated including time of sampling, water temperature, and load of swimmers (Rabi, Khader, Alkafajei, & Aqoulah, 2008). Two previous authors have failed to find any association between bacterial contamination and the pH of the water in swimming pools (Esterman et al, 1984;Rabi et al, 2008). The current research confirmed this lack of association.…”
Section: Discussionsupporting
confidence: 72%
“…Previous research has demonstrated an association between bacterial contamination and the chlorine level in the pools. Other factors also have been implicated including time of sampling, water temperature, and load of swimmers (Rabi, Khader, Alkafajei, & Aqoulah, 2008). Two previous authors have failed to find any association between bacterial contamination and the pH of the water in swimming pools (Esterman et al, 1984;Rabi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This coupled with the probability of soil contamination from rainfall runoff and bacterial biofilm formation along the pipelines or other organic matters could be responsible for the contamination. Swimming pool contamination as a result of high bather density and organic matter contamination is common especially in poorly maintained pools [40,41]. If swimming pools adhered to the National Water and Sewerage Cooperation guidelines, there would be minimal microbial contamination.…”
Section: Discussionmentioning
confidence: 99%
“…If swimming pools adhered to the National Water and Sewerage Cooperation guidelines, there would be minimal microbial contamination. Studies by previous researchers have shown that swimming pools in major hotels and cities in developed nations have low microbial contamination, ranging from 0 to 25% (38)(39)(40)(41)(42)(43). However, the results from the swimming pools in Kampala indicate absolutely very high microbial contamination with heterotrophic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In very soft and poorly buffered waters with an alkalinity of less than about 40 mg of calcium carbonate per litre, pH will be more susceptible to wide fluctuations. In well buffered waters, pH is much less likely to reach extreme values, but the significance of high or low pH for skin reactions and eye irritation will be greater [14]. The temperature of the study areas ranged between 23.7℃ and 26.5℃.…”
Section: Enumeration Of Bacteria In Recreational Water Samplesmentioning
confidence: 99%